Comparing Metabolites and Functional Properties of Various Tomatoes Using Mass Spectrometry-Based Metabolomics Approach - Mun, Ha In; Kwon, Min Cheol; Lee, Na-Rae; Son, Su Young; Song, Da Hye; Lee, Choong Hwan (Frontiers in Nutrition, 2021)
Tomato became one of the world’s most consumed vegetables, and thus, various cultivars have been developed. Therefore, metabolic differences and nutrient contents of various tomatoes are needed to be discovered. To do so, we performed metabolite profiling along with evaluation of morphological and physicochemical properties of 5 representative tomatoes. Common tomato cultivars, bigger and heavier than other tomatoes, contained the higher levels of amino acids, organic acids, and lipids. On the contrary, cherry tomato cultivars contained a relatively higher proportion of phenylpropanoids, lycopene, β-carotene, and α-carotene than the other tomatoes. Also, the highest antioxidant activity, total phenolic and flavonoid contents were observed in cherry tomato cultivars. Furthermore, to understand metabolic distributions in various tomato cultivars, we constructed metabolic pathway map. Through that, it represented the relative higher metabolic flux distribution of most primary metabolite synthetic pathways in common tomatoes, while the secondary metabolite synthetic pathways in cherry tomatoes. Accordingly, these results provide valuable information of different characteristics of various tomatoes which can be considered while purchasing and improving varieties of tomatoes.